A new pathogenicity island carrying an allelic variant of the Subtilase cytotoxin is common among Shiga toxin producing Escherichia coli of human and ovine origin. (17th January 2013) - Michelacci, V.; Tozzoli, R.; Caprioli, A.; Martínez, R.; Scheutz, F.; Grande, L.; Sánchez, S.; Morabito, S.
Abstract: Subtilase (SubAB) is a cytotoxin elaborated by some Shiga Toxin (Stx)‐producing Escherichia coli (STEC) strains usually lacking the locus of enterocyte effacement (LEE). Two variants of SubAB coding genes have been described: subAB 1, located on the plasmid of the STEC O113 98NK2 strain, and subAB 2, located on a pathogenicity island (PAI) together with the tia gene, encoding an invasion determinant described in enterotoxigenic E. coli . In the present study, we determined the entire nucleotide sequence of the PAI containing the subAB 2 operon, termed Subtilase‐Encoding PAI (SE‐PAI), and identified its integration site in the pheV tRNA locus. In addition, a PCR strategy for discriminating the two subAB allelic variants was developed and used to investigate their presence in E. coli strains belonging to different pathotypes and in a large collection of LEE‐negative STEC of human and ovine origin. The results confirmed that subAB genes are carried predominantly by STEC and showed their presence in 72% and 86% of the LEE‐negative strains from human cases of diarrhoea and from healthy sheep respectively. Most of the subAB ‐positive strains (98%) identified possessed the subAB 2 allelic variant and were also positive for tia, suggesting the presence of SE‐PAI. Altogether, our observations indicate that subAB 2 is the prevalent SubAB‐coding operon in LEE‐negative STEC circulating in European countries, and that sheep may represent an important reservoir for human infections with these strains. Further studies are needed to assess the role of tia and/or other genes carried by SE‐PAI in the colonization of the host intestinal mucosa.